Chapter Writing, Copying, Translating Ethiopia as a Manuscript Culture - Bausi, Alessandro (De Gruyter, 2014)
What do Mesoamerica, Greece, Byzantium, Island, Chad, Ethiopia, India, Tibet, China and Japan have in common? Like many other cultures of the world, they share a particular form of cultural heritage: ancient handwritten documents. This volume offers in 16 articles on philological, cultural, and material aspects of manuscripts a common ground across disciplines and cultures.